Technology Development Efficiency and Socio Personal Characteristics of Researchers in Marine Fisheries - J., Charles Jeeva; S., Balasubramaniam; J., Vasanthakumar; V., Geethalakshmi (Fishery Technology, 2025)
This paper deals with the assessment of the technology development efficiency among the researchers in marine fisheries and identification of the influencing socio-personalcharacteristics. The study was conducted among 72 researchers of two premier fisheries research Institutions. The results revealed that the technology development efficiency index was 88.51 ± 10.01. Among the 15 variables studied, the variables viz., communication behaviour, extent of linkages with extension and clientele systems, time utilization in research, participation in professional bodies, in-service training undergone, job satisfaction, job performance and technologies generated had positive and highly significant relationship with the technology development efficiency. The R2 value indicated that all the variables taken together served as cause for explaining 57.60 % of variation in the efficiency level in the technology development process. The present results establish that the technology development process is efficient in marine fisheries